2020
DOI: 10.1038/s41541-020-00243-x
|View full text |Cite
|
Sign up to set email alerts
|

Ad26 vector-based COVID-19 vaccine encoding a prefusion-stabilized SARS-CoV-2 Spike immunogen induces potent humoral and cellular immune responses

Abstract: Development of effective preventative interventions against SARS-CoV-2, the etiologic agent of COVID-19 is urgently needed. The viral surface spike (S) protein of SARS-CoV-2 is a key target for prophylactic measures as it is critical for the viral replication cycle and the primary target of neutralizing antibodies. We evaluated design elements previously shown for other coronavirus S protein-based vaccines to be successful, e.g., prefusion-stabilizing substitutions and heterologous signal peptides, for selecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
341
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 331 publications
(375 citation statements)
references
References 48 publications
10
341
0
5
Order By: Relevance
“… 70 , 71 Some vaccine candidates against SARS-CoV were found to cause pulmonary immunopathology potentially due to Th2-type responses in small animal models, 74 77 and thus one focus for SARS-CoV-2 vaccine development has been to favor a Th1-type response. 72 , 73 A comparison of the ratio of IgG2a/IgG1 antibody titers among antigen groups demonstrated that, except for the RBD, the antigens exhibit a balanced IgG2a and IgG1 response, which was slightly skewed toward IgG2a for both the SΔC-Fer and S-GCN4 groups ( Figure S8A,B ). Notably, the RBD elicited a substantially higher IgG1 response as compared to both IgG2a and IgG2b, suggesting that this antigen in combination with Quil-A/MPLA caused a Th2-biased immune response ( Figure S8B,C ).…”
Section: Resultsmentioning
confidence: 99%
“… 70 , 71 Some vaccine candidates against SARS-CoV were found to cause pulmonary immunopathology potentially due to Th2-type responses in small animal models, 74 77 and thus one focus for SARS-CoV-2 vaccine development has been to favor a Th1-type response. 72 , 73 A comparison of the ratio of IgG2a/IgG1 antibody titers among antigen groups demonstrated that, except for the RBD, the antigens exhibit a balanced IgG2a and IgG1 response, which was slightly skewed toward IgG2a for both the SΔC-Fer and S-GCN4 groups ( Figure S8A,B ). Notably, the RBD elicited a substantially higher IgG1 response as compared to both IgG2a and IgG2b, suggesting that this antigen in combination with Quil-A/MPLA caused a Th2-biased immune response ( Figure S8B,C ).…”
Section: Resultsmentioning
confidence: 99%
“…The induced cell response was Th1-biased rather than Th2-biased, which also demonstrating the safety of the vaccine. Immunogenicity and antigenicity tests in mice revealed that optimization of the S protein (with furin and two proline mutations) increased the proportion of neutralizing antibody binding to nonneutralizing antibody binding [ 41 ]. This study confirmed that optimization of the S protein improved the protective effect of the vaccine.…”
Section: Viral Vector Vaccinesmentioning
confidence: 99%
“… mRNA-1273 Moderna LNP-mRNA S-full length (pre-fusion) Mice [ 22 ] Monkeys [ 31 ] (Challenge: Yes) Phase 1 [ 27 ]: 45 18–55 0/28 25, 100, 250 μg 112, 343, 373 109 PRNT phase 1 [ 28 ]: 20 56–70 0/28 25, 100 μg 116, 402 106 20 > 71 25, 100 μg 121, 317 phase 3: NCT04470427 Viral vector vaccine Ad5-nCoV CanSino Ad5 S-full length Mice [ 38 ] (Challenge: Yes) Phase 1 [ 36 ]: 108 18–60 1 dose 5 × 10 10 , 1 × 10 11 , 1.5 × 10 11 vp 14.5, 16.2, 34 N.A. live virus neutralisation, pseudovirus neutralisation tests Phase 2 [ 37 ]: 508 18–60 1 dose 5 × 10 10 , 1 × 10 11 vp 18.3, 19.5 Phase 3: NCT04526990, NCT04540419 Ad26.COV2.S Janssen Ad26 S-full length (pre-fusion) Mice [ 41 ] Monkeys [ 40 ] (Challenge: Yes) Phase 1/2a [ 42 ]: 402 18–55 0/56 5 × 10 10 vp; 1 × 10 11 vp 214, 243 522 wild-type virus neutralization assay 394 …”
Section: Introductionmentioning
confidence: 99%
“…The full-length spike protein used for immunization (COR200099) (Bos et al, 2020) was produced on Expi293F cells. COR200099 is based on the Wuhan-Hu-1 SARS-CoV-2 strain (MN908947) and stabilized by two point mutations (R682A, R685G) in the S1/S2 junction that knocks out the furin cleavage site, and by two consecutive prolines (K986P, V987P) in the hinge region in S2.…”
Section: Vaccinesmentioning
confidence: 99%
“…Neutralization assays against live SARS-CoV-2 were performed using the microneutralization assay as previously described (Bos et al, 2020), with the modification of a different strain used.…”
Section: Wild Type Virus Neutralization Assay (Wtvna)mentioning
confidence: 99%